Bilateral nephrolithiasis following ingestion of guaifenesin and dextromethorphan - Elizabeth Kim; Michael Perlmutter; Haley Zweber; Joseph Resch (Urology Case Reports, 2023)
Both guaifenesin and dextromethorphan are routinely available nonprescription medications that are also common drugs of abuse amongst young adults. We describe a presentation of guaifenesin and dextromethorphan misuse resulting in acute renal failure due to bilateral nephrolithiasis. The patient underwent placement of bilateral ureteral stents but again formed small renal stones bilaterally. While most renal calculi are not drug-induced, this case highlights the potential for nephrolithiasis after guaifenesin and dextromethorphan ingestion. It suggests that in this combination ingestion multiple mechanisms lead to a prolonged period of nephrolith formation.